ULTRASOUND EXAMINATION IMPACT ON PREGNANCY OUTCOME AMID THREATENED ABORTION: A PROSPECTIVE COHORT STUDY. - Soumya (Student’s Journal of Health Research Africa, 2024)
Background Ultrasound examination plays a crucial role in the management of threatened abortion, aiding in the assessment of fetal viability and the identification of potential complications. Despite its significance, the impact of ultrasonography on pregnancy outcomes in cases of threatened abortion remains to be fully elucidated. In cases where an abortion is threatened, the study aims to evaluate the impact of ultrasonography on pregnancy outcomes. Methods A cohort of 50 pregnant women presenting with symptoms indicative of threatened miscarriage was enrolled. Participants were divided into 3 groups based on pregnancy outcomes: Group I (threatened abortion resulting in pregnancy loss), Group II (threatened abortion with completed pregnancy), and Group III (normal pregnancies serving as the control). Patient demographics, pregnancy outcomes, ultrasound markers, maternal and neonatal outcomes, and the diagnostic performance of sonographic parameters were assessed. Data analysis involved the use of SPSS 20 software. Results The study revealed no significant variations in maternal age, BMI, or parity distribution among the groups. Group I exhibited a 35% pregnancy loss rate, while all participants in Group II completed successful pregnancies. Ultrasound assessments indicated normal parameters in Groups II and III, whereas abnormal sonographic markers were observed in 15% of cases in Group I. Maternal and neonatal outcomes were favorable in Groups II and III, with no notable complications. Abnormal sonographic parameters were associated with late pregnancy complications, and their predictive value for pregnancy loss was notable. Conclusion Ultrasonography significantly influences the management and prediction of pregnancy outcomes in cases of threatened abortion. Early detection of abnormal sonographic markers facilitates risk stratification and guides clinical decision-making, ultimately improving maternal and neonatal outcomes. Recommendations Routine ultrasound examination should be considered in cases of threatened abortion to enhance pregnancy monitoring and improve outcomes.